Nurturing financial literacy skills among students At Sentul Guidance Center Kuala Lumpur Malaysia - Charly Marlinda; Dea Natassa; Dhea Amanda Aulia Putri; Melisa Melisa; Armansyah Armansyah; Shohehuddin Shohehuddin (International Journal of Community Engagement and Development, 2023)
Providing education about the importance of financial literacy to students aims to ensure that students are able to manage their money intelligently, such as saving. All financial literacy service activities are adjusted to the type of educational media using methods adapted to several activity stages, namely the preparation stage, the implementation stage of service activities carried out at the Kuala Lumpur Indonesian School. Activities carried out include providing education to students on the priority scale of needs, how to save and asking several questions to determine students' understanding and the evaluation stage of activities.